La valeur prédictive de resume de soi et de la congruence personne-champ d'études dans la transition études-travail: Plus de questions que de réponses - Bujold, Charles; Fournier, Geneviève; Lambert, Léo Daniel (Canadian Journal of Counselling and Psychotherapy, 2009)
The research reported here was aiming at testing the predictive value of self-esteem and personfield of study congruence in the school to work transition, and the role of gender, program of study and age in this prediction. Another of its goals was to examine the relationship between an increase in the sense of personal and social identity and an increase in self-esteem. Results in line with the theoretical expectations have been observed in relation to the latter aspect, whereas the hypotheses concerning the predictive part of the study have been to a large extent not supported.